Indução à maturação final, ovulação e fertilização do cachara, Pseudoplatystoma fasciatum, em cativeiro - Leonardo, Antonio Fernando Gervásio [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
In the months of January 2001 and January 2002, females of cachara, Pseudoplatystoma fasciatum, were selected during their first and second gonadal maturation (2 years and 7 months old and 3 years and seven months old, respectively) according to the association between the external anatomic characteristics and internal, showing distribution of oocyte diameter frequency with a single mode of 937.5 mm; 82.5 % of central nuclei and 17.5 % of eccentric nuclei. Histologically, it was observed that the majority of oocytes were in final maturation. Nine females in first maturation received 2 doses of carp pituitary extract (CPE), 0.5 mg/kg and 5.0 mg/kg (T1); seven received 2 doses of hCG, 5 and 10 IU/g (T2); five received doses of carp pituitary extract 0.5 mg/kg and hCG 5IU/g (T3); four received 0.9 % saline (T4). Nine females from T1 and seven from T2 presented oocytes with the same diameter at the moment of oocyte release; 100 % with germinal vesicle breakdown and fertilization rate of 53.44 + 18.3 and 54.81 + 11.8 %; larvae number of 165,330 + 94.1 and 158,570 + 20.6, respectively. The five females from T3 didn't respond to the hormonal treatment. The four females from T4 belonged to the control group. In January 2002, 6 of the 15 selected females that were going through the second cycle received T1; 5 received T2; and 4 received T4, showing oocyte diameters similar to the ones in the first maturation. On the third samples, the females from T1 showed mode shift to the right and modal diameter of 1062.5mm; the females from T2 presented diameters ranging from 937.5mm to 1125.0mm; fertilization rates of 56.08 + 30.9 and 81.90 + 17.3 %; 364,547 + 244 and 633,129 + 190 larvae, respectively. Under light microscopy, it was noticed that the oocytes were similar to the ones at the previous stage. A better efficiency of T2 was verified on the second maturation females, considering the fertilization rates ...

Nos meses de janeiro de 2001 e 2002, as fêmeas de cachara, Pseudoplatystoma fasciatum, de 1ª e 2ª maturação gonadal (2 anos e 7 meses e 3 anos e 7 meses), respectivamente, mantidas em cativeiro, foram selecionadas pela associação da característica externa anatômica, com internas, apresentando distribuições de freqüência porcentual dos diâmetros dos ovócitos com uma única moda de 937,5 μm; 82,5% dos núcleos centrais e 17,5% excêntricos. Histologicamente, pôde-se observar que a maioria dos ovócitos encontravam-se em fase de maturação final. Nove fêmeas de 1ª maturação, receberam 2 doses de extrato de hipófise de carpa (HC), 0,5 mg/Kg e 5,0 mg/Kg (T1); 7, com 2 doses de hCG, 5 e 10 IU/g (T2); 5, com 0,5 mg/Kg HC e 5 IU/g hCG/g (T3); 4 com solução salina 0,9% (T4). As 9 fêmeas do T1 e 7 do T2, no momento da liberação dos ovócitos, apresentaram ovócitos com o mesmo diâmetro; 100% com quebra da vesícula germinativa e taxas de fertilização de: 53,44 + 18,3 e 54,81 + 11,8 %; número de larvas de 165.330 + 94,1 e 158.570 + 20,6, respectivamente. As 5 fêmeas do T3 não responderam ao tratamento hormonal. As fêmeas do T4 pertenciam ao grupo controle. Em janeiro/02, das 15 fêmeas selecionadas, que se encontravam no 2º ciclo, 6 receberam o T1, 5 o T2 e 4 T4, apresentando diâmetros dos ovócitos semelhantes às de 1ª maturação. Nas 3as amostras, as fêmeas do T1 apresentaram deslocamento das modas para à direita, diâmetro modal de 1062,5 μm e as do T2, com diâmetros de 937,5 a 1125,0 μm, taxas de fertilização de 56,08 + 30,9 e 81,90 + 17,3 % e 334.547 + 244 e 633.129 + 190 larvas, respectivamente. Em microscopia de luz, notou-se que os ovócitos eram semelhantes aos da fase anterior. Pôde-se constatar maior eficiência do T2, nas fêmeas de 2ª maturação, quanto às taxas de fertilização e número de larvas obtidos durante o período estudado
Keywords: Peixe - Reprodução; Fecundidade; Ovulação - Indução; Femea; Hormonios; Oócitos; Hormones